In vitro anticandidal activity and gas chromatography-mass spectrometry (GC-MS) screening of Vitex agnus-castus leaf extracts - Ababutain, Ibtisam Mohammed (PeerJ, 2021)
BACKGROUND: Candida infections are becoming more drug resistant; it is necessary to search for alternative medications to treat them. Therefore, the present study estimates the anticandidal activity of Vitex agnus-castus (VA-C) leaf extracts. METHODS: We used the agar well diffusion method to assess the anticandidal activity of three different VA-C leaf extracts (ethanol, methanol, and water) against three Candida species (Candida tropicalis, Candida albicans, and Candida ciferrii). The minimum inhibitory concentration (MIC) was estimated using the two-fold dilution method and the minimum fungicidal concentration (MFC) was determined using the classic pour plate technique. The MFC/MIC ratio was calculated to estimate the microbicidal or microbiostatic activity. A gas chromatography mass spectrometer was used to screen the phytochemicals of the VA-C leaf extracts (ethanol, methanol, and water). RESULTS: All VA-C extracts ethanol, methanol, and water were significantly inhibited the growth of the test Candida species and the inhibition activity depended on the solvent used and the Candida species. The results showed that C. tropicalis was the most highly inhibited by all extracts followed by C. albicans and C. ciferrii. The MIC values were 12.5–25 µg/ml, and MFC values were 25–100 µg/ml. The ratios of MFC/MIC were two-fold to four-fold which was considered candidacidal activity. Ninety-five phytochemical compounds were identified by the GC-MS assay for the VA-C leaf extracts. The total number of compounds per extract differed. Methanol had 43 compounds, ethanol had 47 compounds, and water had 52 compounds. The highest compound concentrations were: 4,5-Dichloro-1,3-dioxolan-2-one in ethanol and methanol, 1H-Indene, 2,3-dihydro-1,1,2,3,3-pentamethyl in ethanol, Isobutyl 4-hydroxybenzoate in methanol, and Benzoic acid and 4-hydroxy- in water. These phytochemical compounds belong to different bioactive chemical group such as polyphenols, fatty acids, terpenes, terpenoids, steroids, aldehydes, alcohols, and esters, and most of which have anticandidal activity. CONCLUSIONS: VA-C leaf extracts may be useful alternatives to anticandidal drugs, based on their effectiveness against all test Candida species at low concentrations. However, appropriate toxicology screening should be conducted before use.